Encapsulated bacteriophages in alginate-nanohydroxyapatite hydrogel as a novel delivery system to prevent orthopedic implant-associated infections - Barros, Joana Alberta Ribeiro (2020)
An innovative delivery system based on bacteriophages-loaded alginate-nanohydroxyapatite hydrogel was developed as a multifunctional approach for local tissue regeneration and infection prevention and control. Bacteriophages were efficiently encapsulated, without jeopardizing phage viability and functionality, nor affecting hydrogel morphology and chemical composition. Bacteriophage delivery occurred by swelling-disintegration-degradation process of the alginate structure and was influenced by environmental pH. Good tissue response was observed following the implantation of bacteriophages-loaded hydrogels, sustaining their biosafety profile. Bacteriophages-loaded hydrogels did not affect osteoblastic cells' proliferation and morphology. A strong osteogenic and mineralization response was promoted through the implantation of hydrogels system with nanohydroxyapatite. Lastly, bacteriophages-loaded hydrogel showed excellent antimicrobial activity inhibiting the attachment and colonization of multidrug-resistant E. faecalis surrounding and within femoral tissues. This new local delivery approach could be a promising approach to prevent and control bacterial contamination during implantation and bone integration.